The Relationship between Physical Activity and The Level of Physical Fitness of Pencak Silat Athletes - Mubarak, Jamil; Yudistira, Sigit; Solechah, Siti Aisyah; Norhasanah, Norhasanah (Sport and Nutrition Journal, 2023)
This study analyzed the relationship between macronutrient intake, hydration status, physical activity, and the physical fitness level of Pencak silat athletes in Banjarbaru. This analytical observational study used a cross-sectional design involving 30 pencak silat athletes selected using a total sampling technique. The research instruments included questionnaires, 24-hour food recall forms, a self-urine examination (PURI), a physical activity questionnaire, and a 12-minute running test. Data were analyzed using the Spearman Rank test. The results of this study indicated that most athletes had protein, fat, and carbohydrate deficiencies, moderate hydration status, and very light physical activity levels. It can be concluded that macronutrient intake, namely protein (p=0.264), fat (p=0.643), carbohydrates (p=0.101), and hydration status (p=0.264), had no association with the physical fitness levels of pencak silat athletes, while physical activity (p =0.010) had an association with the physical fitness level of Pencak silat athletes. Athletes are recommended to continue to pay attention to macronutrient intake and hydration status as needed because they also play an essential role in fitness apart from physical activity.